Indoor air pollution control - Godish, Thad. (Chelsea, Mich. Lewis Publishers, 1989)
This book is designed to provide the practical information and data needed for indoor air pollution control! Presented early in the book is theory as support for the applications that follow; including a synthesized review of the significant literature on controlling air pollution. Practical applications-largely from the author's own experience-deal with 1) How to conduct indoor air quality investigations in both residences and public access buildings, 2) Indoor air quality mitigation practice, and 3) Case histories. This book will be very useful to consultants and other professionals who grapple to solve real world problems. And it will make an excellent textbook for new courses in indoor air quality. Indoor Air Pollution Control will be used for control and prevention of contaminated air in homes, apartment buildings, office buildings (large and small), hospitals, auditoriums, and other public buildings.
Includes bibliographies and index.
Keywords: Indoor air pollution